Evaluation of the Influence of Frequency of Milk Collection and Milking Dayshift on the Microbiological Quality of Raw Milk. (21st May 2018) - Reguillo, Lucía; Hernández, Manuela; Barrientos, Elisabeth; Perez-Rodriguez, Fernando; Valero, Antonio
Abstract : The aim of this study was to analyze the influence of milk collection frequency (24 h versus 48 h) and milking dayshift (morning and evening) on total mesophilic aerobic bacteria (MAB) and psychrotrophic bacteria (PSY) counts in raw milk samples. MAB counts were determined by flow cytometry (BactoScan) and PSY counts by the plate counting agar method. An univariate statistical analysis was performed to find out significant differences among the studied factors. Results obtained showed that collecting milk every 24 h was effective in reducing MAB and PSY counts by 32 and 18%, respectively, compared to 48 h milk collection. This positive impact allowed reducing up to 4°C the temperature of the heat treatment in the dairy industry, thus involving energy savings of 22%. Milking during the mornings showed a significant reduction of MAB counts in comparison to milking performed during the evenings (P < 0.05 ). These results are highly useful for the improvement of milk quality through the optimization of collection and milking systems set at primary production.